Artemisinin Stimulates Neuronal Cell Viability and Possess a Neuroprotective Effect In Vitro - Sergey A. Pukhov; Alexey V. Semakov; Nadezhda E. Pukaeva; Olga A. Kukharskaya; Tatyana V. Ivanova; Viktoriya S. Kryshkova; Sergey O. Bachurin; Michail S. Kukharsky (Molecules)
Artemisinin is a sesquiterpene lactone derived from the plant Artemisia annua L., renowned for its antimalarial activity. Based on this compound, various derivatives and analogues have been obtained that exhibit diverse biological activities, including clinically approved drugs. Recently, increasing evidence has highlighted the neuroprotective potential of artemisinin. In this study, we evaluated the effects of artemisinin on the viability of neuronal-like cells, including primary hippocampal neuronal cultures. Artemisinin exhibited a stimulating effect on SH-SY5Y and HEK-293 cells and enhanced the survival of primary neurons at low concentrations (1 µM). In contrast, artemisinin derivatives, such as dihydroartemisinin, anhydrodihydroartemisinin, and artemisitene, did not display similar stimulatory activity, suggesting that the intact lactone ring is crucial for this property. Furthermore, artemisinin demonstrated a protective effect against endoplasmic reticulum (ER) stress induced by the proteasome inhibitor MG132 in SH-SY5Y cells. However, it did not exhibit protective activity against oxidative stress induced by sodium arsenite. Additionally, artemisinin effectively inhibited the aggregation of mutated TDP-43 protein in transfected SH-SY5Y cells. These findings suggest that artemisinin exerts neuroprotective effects by targeting key molecular pathways associated with neurodegeneration, offering potential therapeutic insights for related conditions.